2021
DOI: 10.1002/adfm.202102275
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermopower and Nernst Signal of High‐Mobility Dirac Carriers by Fermi Level Tuning in the Layered Magnet EuMnBi2

Abstract: In the last 15 years, conducting materials, whose low energy excitation exhibits linear energy-momentum dispersion of relativistic Dirac fermions, have attracted much attention due to

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Various studies in NbP, TaP, NbAs, and TaAs have reported prominent properties of MR in the range of 10 4 %-10 6 % [9,16,18,19,37] as well as Nernst thermopower (S xy ) of ≈1 × 10 3 μV K -1 , [16,21,23] which represent remarkable progresses among different types of topological semimetals. [35,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Taking NbP as the example, the MR of single-crystal NbP reaches an extremely large value of 8.5 × 10 5 % at 1.85 K in a magnetic field of 9 T, [9,37] which is ascribed to the interplay of overlapped conduction and valence bands, linear band dispersion and ultra-high carrier mobility (μ) of 5 × 10 6 cm 2 V -1 s -1 . The ultra-high μ and the effective compensation of electrons and holes are two critical factors responsible for the prominent S xy in NbP, and thus, a usually large Nernst thermopower (S xy ) exceeding 800 μV K -1 could be obtained at 9 T and 109 K, [21] leading to a very large Nernst thermoelectric power factor (PF xy ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in NbP, TaP, NbAs, and TaAs have reported prominent properties of MR in the range of 10 4 %-10 6 % [9,16,18,19,37] as well as Nernst thermopower (S xy ) of ≈1 × 10 3 μV K -1 , [16,21,23] which represent remarkable progresses among different types of topological semimetals. [35,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] Taking NbP as the example, the MR of single-crystal NbP reaches an extremely large value of 8.5 × 10 5 % at 1.85 K in a magnetic field of 9 T, [9,37] which is ascribed to the interplay of overlapped conduction and valence bands, linear band dispersion and ultra-high carrier mobility (μ) of 5 × 10 6 cm 2 V -1 s -1 . The ultra-high μ and the effective compensation of electrons and holes are two critical factors responsible for the prominent S xy in NbP, and thus, a usually large Nernst thermopower (S xy ) exceeding 800 μV K -1 could be obtained at 9 T and 109 K, [21] leading to a very large Nernst thermoelectric power factor (PF xy ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been revealed that the exchange coupling strongly affects the thermoelectric phenomena (Seebeck and Nernst effects) as well 56 . These facts indicate that various electrical and thermal transport phenomena are tunable by controlling the Dirac band (splitting) via the magnetic Eu layers in this material.…”
Section: Dirac Fermion Coupled With Magnetic Order In Eumnbimentioning
confidence: 99%
“…We have also demonstrated the control of the spin-valley state for BaMnX 2 via the chemical substitution of the X site as a result of the modulation of the lattice distortion and spin-orbit coupling. Furthermore, the partial substitution of the divalent A site with a trivalent one in the block layer leads to electron doping in the Dirac fermion layer, enabling Fermi level tuning across the charge neutral point (not reviewed here in detail) 56 . In addition to magnetic field and chemical substitution, it has been recently predicted that mechanical strain could also significantly affect the band structure and/or topology owing to the high sensitivity to lattice distortion 100 .…”
Section: Tunable Spin-valley Couplingmentioning
confidence: 99%
“…Furthermore, the [MnBi 4 ] ([MnSb 4 ]) tetrahedral layers in the structure also offer an arena to investigate the interplay between magnetic order and topological properties . Both density functional theory and angle-resolved photoemission spectroscopy demonstrated the anisotropic Dirac cones in momentum space for A MnBi 2 and A MnSb 2 . ,, This intriguing band structure leads to a series of novel quantum properties including giant magnetoresistance (MR), magnetothermopower, valley-selective interlayer conduction, and spin-valley locking, which are of relevance for designing new-generation electronic devices with high performance.…”
Section: Introductionmentioning
confidence: 99%